PRE-SERVICE ENGLISH TEACHERS IN BLENDED LEARNING ENVIRONMENT IN RESPECT TO THEIR LEARNING APPROACHES - Yilmaz, M. Betuel; Orhan, Feza (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2010)
Blended learning environment (BLE) is increasingly used in the world, especially in university degrees and it is based on integrating web-based learning and face-to-face (FTF) learning environments. Besides integrating different learning environments, BLE also addresses to students with different learning approaches. The 'learning approach' categorizes individuals as 'surface learners' and 'deep learners'. This study investigated whether the academic performance and the satisfaction levels of the pre-service English teachers varied in respect to their learning approaches in a blended learning environment. At the end of the study it was found that a) academic performance scores of the students in the BLE did not show statistically significant difference between deep and surface learners, b) the average satisfaction level with the BLE of deep learner students was statistically significantly higher than the average of surface learner students. Based on these findings, it can be concluded that pre-service English Language teachers were in general highly satisfied with the BLE. In addition, it can be stated that the courses which are designed for the BLE contribute to the achievement of the students with surface learning approach. Based on these conclusions, BLE is advised for training of pre-service English Language teachers with different learning approaches.
Keywords: Blended learning; Learning approach; Teacher training; STUDENTS; PERSONALITY; CONCEPTIONS; PSYCHOLOGY; ONLINE; Education & Educational Research